2014
DOI: 10.5897/ajmr12.1663
|View full text |Cite
|
Sign up to set email alerts
|

Activity of beta-lactam antibiotics and production of beta-lactamases in bacteria isolated from wound infections in Brazzaville, Congo

Abstract: To determine the mechanism of bacterial beta-lactam resistance, 165 bacteria isolated from wounds of hospitalized patients composing of: 42 Staphylococcus aureus, 37 Pseudomonas aeruginosa, 23 Escherichia coli, 22 Proteus, 12 Klebsiella, 10 coagulase-negative staphylococci (CNS), eight Enterobacter, six Citrobacter, five Providencia were tested for their sensitivity to beta-lactams and their production of beta-lactamases. The antibiotic susceptibility was considered by the method of the standard diffusion on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…In this study, the rates of resistance to ceftriazone and imipenem in E. coli strains were 0% and 12.5%, respectively. These frequencies are in disagreement with those reported by Mpelle et al [11] on E. coli, whose respective rates are 79.07% and 0%, and by Moyen et al [13] 73.9% and 4.3%. Oubrim et al [14] reported a zero resistance rate for the same antibiotics tested.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In this study, the rates of resistance to ceftriazone and imipenem in E. coli strains were 0% and 12.5%, respectively. These frequencies are in disagreement with those reported by Mpelle et al [11] on E. coli, whose respective rates are 79.07% and 0%, and by Moyen et al [13] 73.9% and 4.3%. Oubrim et al [14] reported a zero resistance rate for the same antibiotics tested.…”
Section: Discussioncontrasting
confidence: 83%
“…We reported 100% resistance rates in E. coli to amoxicillin, amoxicillin + clavulanic acid, cefalotin, ceftazidime and nalidixic acid. Lower percentages of resistance were reported by Passerat et al [12] 25%, 15%, 20%, 0% and 25% respectively; Moyen et al [13] reported 100%, 87%, 87% for amoxicillin, amoxicillin acid/clavulanic acid, cefalotin and ceftazidime. In this study, the rates of resistance to ceftriazone and imipenem in E. coli strains were 0% and 12.5%, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…All E. coli strain isolates were resistant to Cefrazidime. This differs from rate of resistant of 77.3% reported by [19] on E. coli isolated at the CHUB. [20] in the Republic of Congo working on E. coli isolated from CHUB inpatients and outpatients reported resistance rates of 46.51%, 37.20%, 34.88% 13.95% and 46.51% respectively for piperacillin-tazobactam, cefepime, gentamicin, ciprofloxacin and fosfomycin in the extended-spectrum beta-lactamase producing strains.…”
Section: Discussioncontrasting
confidence: 81%
“…Classes A and D enzymes are commonly found in Africa with a predominance of blaCTX-M-15 (Storberg, 2014). In Congo-Brazzaville, a prevalence of 73.8% of E. coli strains harboring beta-lactamase phenotype was reported (Moyen et al, 2014). To our knowledge, no study has been performed on the characterization of Enterobacteriaceae resistance genes.…”
Section: Introductionmentioning
confidence: 96%